2022
DOI: 10.1111/clr.13981
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a chairside, fused deposition modeling three‐dimensional‐printed, single tooth surgical guide for implant placement: A randomized controlled clinical trial

Abstract: Purpose: To compare the accuracy of chairside, fused deposition modeling (FDM) three-dimensional (3D)-printed surgical guides with that of stereolithographic guides for implant placement in single edentulous sites within a clinical setting. Materials and Methods:A total of 28 participants with 30 single posterior edentulous sites were included. The sites were randomized into a FDM 3D-printed surgical guide group (test) or stereolithographic guide group (control) of equal size (n = 15).In both groups, digital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
1
3
0
1
Order By: Relevance
“…It is noteworthy that although all crowns manufactured herein were tried in, only the crowns designed by a CAD-CAM technologist were ultimately installed and followed up. The favorable questionnaire outcomes obtained by the crowns designed by the dentist are in agreement with several studies in the literature describing the usefulness and predictability of chairside steps of digital workflows [15][16][17][18][19][20][21][22][23][24][25], including for rehabilitations involving dental implant therapy [26][27][28][29][30][31][32][33]. This is a clinically relevant finding, since the dentist usually plays a major role in the design and manufacture of the CAD-CAM restorations when a chairside digital workflow is performed.…”
Section: Discussionsupporting
confidence: 86%
“…It is noteworthy that although all crowns manufactured herein were tried in, only the crowns designed by a CAD-CAM technologist were ultimately installed and followed up. The favorable questionnaire outcomes obtained by the crowns designed by the dentist are in agreement with several studies in the literature describing the usefulness and predictability of chairside steps of digital workflows [15][16][17][18][19][20][21][22][23][24][25], including for rehabilitations involving dental implant therapy [26][27][28][29][30][31][32][33]. This is a clinically relevant finding, since the dentist usually plays a major role in the design and manufacture of the CAD-CAM restorations when a chairside digital workflow is performed.…”
Section: Discussionsupporting
confidence: 86%
“…4 . Overall, the nineteen RCTs [ 12 , 22 , 26 , 42 , 54 , 59 , 64 66 , 69 , 72 , 74 77 , 79 82 ] were assessed using RoB-2. Nine presented a “low risk” of bias, while eight presented “some concerns”.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, tooth-supported computer-aided static implant surgery by surgical templates has evidenced a predictable treatment outcome for dental implant placement, showing statistically significant differences (p < 0.05) with respect to the number of teeth [28]. Moreover, fixation pins have been also recommended to attach the surgical templates to the maxilla during the drilling procedure; however, Pessoa et al (2022) reported that the use of surgical templates with or without fixing pins for dental implant placement provided predictable treatment outcomes [29]. In the present study, the surgical template designed for the interproximal enamel reduction procedure did not include fixing pins because it was tooth-supported by fully dentated anatomical-based upper and lower experimental cast models; additionally, the operator checked the surgical template stability before use.…”
Section: Discussionmentioning
confidence: 99%